Late Miocene and Pliocene pikeperches (Teleostei, Percidae) of southeastern Europe. Issue 3 (3rd May 2016) - Kovalchuk, Oleksandr M.; Murray, Alison M.
ABSTRACT: Freshwater fish fossils representing two or more species of Sander ( S. lucioperca, S. svetovidovi, and Sander sp.) and Leobergia zaissanica are reported from a number of localities in Southeastern Europe. These localities sample the late Miocene through early Pliocene, when the landscape was undergoing major changes associated with the collision of the Afro-Arabian and Eurasian plate. This caused changes to ocean circulation with the closing of the Tethys, as well as uplift of mountain ranges in Europe. This was also a period of significant climate change, with the onset of polar glaciation causing a cooling, drying phase globally but also specifically documented for this region. The fossil fish material documents the presence of percids during this time and also the apparent loss of Leobergia in the Pliocene. The loss of Leobergia may well have been caused by a lower tolerance to cool climates of this genus compared to Sander, a genus with five extant species. Citation for this article: Kovalchuk, O. M., and A. M. Murray. 2016. Late Miocene and Pliocene pikeperches (Teleostei, Percidae) of southeastern Europe. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2016.1100999.